Pengaruh Pembelajaran Daring Terhadap Perkembangan Sosial-Emosional Anak Usia 5-6 Tahun di Kecamatan Serang, Kota Serang, Banten - Fitri Febriyanti; Laily Rosidah; Fahmi Fahmi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Socio-emotional development is a condition in which children are able to interact with other people in the community such as recognizing their own feelings and controlling themselves, being able to adapt to others, having a sense of responsibility, obeying rules, self-regulating, responding, and respecting rights and opinions. other people. This study aims to determine the effect of online learning on the socio-emotional development of children aged 5-6 years. This study uses a type of quantitative survey research methodology by distributing online questionnaires assisted by using a google form. Data were obtained using a questionnaire distributed to respondents with a sample of 60 teachers in Serang District and currently carrying out online learning. The results of this study indicate that the correlation coefficient of online learning on the socio-emotional development of children aged 5-6 years shows a number of 0.697 which means it has a strong level of influence, because it is in the interval 0.61 to 0.80. While the probability number 0.000 <0.05, it can be concluded that there is an influence between 2 variables, so H0 is rejected and H1 is accepted. The linear regression equation is Y= 43.352 + 0.351 which states that every 1% addition of the value of online learning will increase the value of social-emotional development by 0.351. Therefore, the online learning variable on the socio-emotional development variable has an influence.